ANALISIS PENGARUH JUMLAH TRANSPORTASI DARAT, INFRASTRUKTUR DAN JUMLAH PENDUDUK TERHADAP PRODUK DOMESTIK BRUTO (PDB) INDONESIA - Bimo Wicaksono (2021)
Gross Domestic Product is considered the best measure of the performance of the national economy used to describe and assess the level of economic growth and the welfare of the people of a country. Many variables are used to influence Gross Domestic Product, such as Transportation, Infrastructure, and Population. This study aims to determine the effect of Transportation, Infrastructure, and Population on Gross Domestic Product in Indonesia. This study uses data from 1988 to 2018. The method used in this study is a multiple linear regression analysis model using the OLS method. The findings in this study indicate that (1) there is a positive effect between transportation on Indonesia's economic growth (2) infrastructure has a positive effect on Indonesia's economic growth (3) Population has a positive effect on Indonesia's economic growth.